Digital Forensic Challenges in the Cloud Computing Environment - Samy, GN; Shanmugam, B; Maarop, N; Magalingam, P; Albakri, SH; Sundresan Perumal (Springer International Publishing Ag, 2024)
Indexed by WOS/ Scopus